2019
DOI: 10.1186/s12905-019-0711-8
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean scar endometriosis: presentation of 198 cases and literature review

Abstract: BackgroundCesarean scar endometriosis (CSE) is the most common type of abdominal wall endometriosis (AWE). The aim of this study was to systematically identify the clinical features of CSE and recommend precautionary measures.MethodsA large, retrospective study was undertaken with CSE patients treated surgically at our hospital between January 2005 and December 2017.ResultsA total of 198 CSE patients were enrolled, with a mean age of 32.0 ± 4.0 years. The main complaint of the patients was abdominal mass (98.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
102
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 24 publications
11
102
0
8
Order By: Relevance
“…These observations agree with previous studies conducted on cancer cells suggesting that collagen content alone can increase the invasive cellular phenotype 37,38 . In conclusion, our results provide clear support for the clinical data suggesting that endometriosis commonly implants in scars 34 , including surgical scars such as that left behind by the Csection 33 . We next show that the collagen I defects caused by stromal cells arise due to matrix degradation via MMPs rather than due to cellular contraction and traction forces.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These observations agree with previous studies conducted on cancer cells suggesting that collagen content alone can increase the invasive cellular phenotype 37,38 . In conclusion, our results provide clear support for the clinical data suggesting that endometriosis commonly implants in scars 34 , including surgical scars such as that left behind by the Csection 33 . We next show that the collagen I defects caused by stromal cells arise due to matrix degradation via MMPs rather than due to cellular contraction and traction forces.…”
Section: Discussionsupporting
confidence: 83%
“…In particular, the invasive modes cells adopted using the 3-D spheroid model but not single cells on ECM could, for the first time, reproduce collective-migration phenotypes previously identified only through histological and clinical observations, further confirming the relevance of this model. Several clinical studies suggested endometriosis can only implant in damaged tissues 33,34,35 . To investigate this in vitro, we mimicked the intact tissue using the basement membrane mimic Matrigel and scar-tissue mimic collagen I.…”
Section: Discussionmentioning
confidence: 99%
“…Most of abdominal wall endometriosis has been reported to be associated with prior cesarean section, followed by uterine surgery . It is biologically possible because there is an opportunity for the inoculation of endometrial cells to the peritoneal cells from hysterotomy . Twenty‐one cases of laparoscopic port site endometriosis have been reported (Table ) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the possibility of abdominal endometriosis unrelated to previous surgery cannot be completely ruled out, abdominal endometriosis other than umbilical or inguinal lesions is highly associated with previous surgery . In addition, tumor location corresponded to the trocar site.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of functional endometrial tissues outside the uterine cavity is termed as endometriosis. It is a gynecological disorder depended on the sex hormone 1 .…”
Section: Introductionmentioning
confidence: 99%